A Metalinguistic Approach for School-Based Speech and Language Intervention - Oakland, Adriana; Holte, Gayle; Samelson, Vicki M. (My University, 2017)
Students with speech-language disorders often struggle to generalize their newly learned skills to the classroom and home environments. We hypothesize one reason this is challenging is because many speech-language pathologists (SLPs) are teaching the skills to improve speech and language, but not the strategies to generalize those skills. The aim of this single-subject pilot study was to find out if using a metalinguistic therapy approach (Think Alouds) would help a 4th grade student become a more active participant and generalize skills more readily.
Color poster with text, tables, and graphs.
Keywords: Posters; Metalinguistics; Speech disorders; Speech-language pathologists